Future Mindedness in Single Middle Adult Women - Febby Listya Ekayanti; Nurchayati (Analitika: Jurnal Magister Psikologi UMA, 2023)
This article examines future mindedness among single middle adult women. In line with the dominant culture, most parents in Indonesia rely on their children for support in old age. Some women, however, choose to remain single and childless. This article focuses its exploration on the ways in which these unmarried, childless women plan and prepare for their lives in old age. Using the case-study approach and employing, as its theoretical framework, Seginer’s concept of future mindedness, we collected our data through semi-structured interviews with four women, aged 42 to 55, who served as research participants. After triangulating the data, we interpreted it using the thematic analysis method. Our study produced four findings. First, comfortable with being single, three of the four women had no desire to marry. Second, taking a positive view of old age, and knowing fully well that their kinfolk will take care of them in their advanced years, all the four participants do not worry about old age. Third, none of their relatives has put pressure on them to marry. Fourth, personality and family support appear to play a key role in these women’s choice to live a life of celibacy. In sum, unmarried middle-aged women are happy with their status and have plans for life in old age, including where to live and how to get elderly care.